In intergroup conflict, self-sacrifice is stronger among pro-social individuals, and parochial altruism emerges especially among cognitively taxed individuals - Dreu, Carsten K. W. De; Dussel, D. Berno; Velden, Femke S. Ten (Frontiers in Psychology, 2015)
Parochial altruism is decomposed in a tendency to benefit the in-group along with a tendency to ignore, derogate, and harm rivaling out-groups. Building off recent work suggesting that decisions to cooperate can be relatively fast and intuitive, we examine parochial altruism in intergroup conflict when cognitive deliberation is rendered difficult or not. Predictions were tested in an experiment using an incentivized Intergroup Prisoner’s Dilemma—Maximizing Differences Game (IPD-MD) with ninety-five subjects classified as either pro-social or pro-self being randomly allocated to high vs. low impulse-control conditions. Results showed, first of all, that decisions to contribute and self-sacrifice were made faster than decisions not to contribute, and that longer decision time associated with less positive expectations of in-group members. Second, we observed that lowering impulse control with a difficult rather than easy Stroop Task increased the amount contributed to a pool that benefited in-group members while harming out-group members; thus reducing deliberation increased parochial altruism. Finally, results replicated earlier work showing that especially pro-social (versus pro-self) individuals contributed more to the in-group and did not lower their contributions to the between-group pool that benefitted their in-group and, simultaneously, hurt the out-group. This pattern emerged independent of their impulse control. Thus, (in-group bounded) cooperation is more prominent among individuals with strong rather than weak other-regarding preferences. Moreover, the intuitive tendency to cooperate may have evolved in the context of intergroup conflict and therefore is sharp-edged—in-group bounded and including willingness to aggress out-groups.